The effect of educational program based on beliefs, subjective norms and perceived behavior control on doing pap-smear test in sample of Iranian women - Ali Khani Jeihooni; Hanieh Jormand; Pooyan Afzali Harsini (BMC, 2021)
Abstract Objective Cervical cancer is considered treatable as long as it is detected early and managed effectively. Pap smear test is a screening tool that plays an important role in the early detection, prevention and can prevent any early cervical cell changes from becoming cancer. This study aims to survey the effect of educational programs based on beliefs, subjective norms, and perceived behavior control on doing the pap-smear test in a sample of Iranian women. Materials and methods This experimental interventional study was performed on 300 women admitted to Fasa City, Fars Province, Iran health centers in 2018-2019. A questionnaire consisting of demographic information, knowledge, Health Belief Model, and Theory of Planned Behavior constructs were used to measure on doing of Pap smear test in women before and after 6 months' educational intervention. Results The results revealed that 6 months after the intervention, 108 women (72%) in the experimental group and only 9 women (6%) in the control group received the Pap smear test. Conclusions The current research results revealed that education based on the combination of the health Belief model and theory of planned behavior might be promoting participation and an increasing rate of receiving Pap smear tests in women.